Systemic calcinosis in a Quarter Horse gelding homozygous for a myosin heavy chain 1 mutation. (8th July 2022) - Sponseller, Beatrice T.; Wong, David M.; Ruby, Rebecca; Ware, Wendy A.; Wilson, Scott; Haynes, Joseph S.
Abstract: Case Description: A 9‐year‐old Quarter Horse gelding was presented for lethargy, decreased appetite, polyuria and polydipsia (PU/PD), and severe muscle wasting suggestive of immune‐mediated myositis. Clinical Findings: The horse displayed lethargy, fever, tachyarrhythmia, inappetence, PU/PD, and severe epaxial and gluteal muscle wasting. Clinicopathologic findings were consistent with previously reported cases of systemic calcinosis in horses, including increased muscle enzyme activity, hyperphosphatemia, increased calcium‐phosphorus product, hypoproteinemia, and an inflammatory leukogram. A diagnosis of systemic calcinosis was established by histopathologic evaluation of biopsy specimens from skeletal muscle, lung, and kidney. Treatment and Outcome: Symptomatic treatment was complemented by IV treatment with sodium thiosulfate to reverse calcium‐phosphate precipitation in soft tissue and PO aluminum hydroxide to decrease intestinal phosphorus absorption and serum phosphorus concentration. Clinical Relevance: This is the first report in the veterinary literature of an antemortem diagnosis of systemic calcinosis in the horse that was successfully treated and had favorable long‐term outcome.